The Role of the School Community in Encouraging Student Multiculturalism Through Islamic Religious Education at State Elementary School No. 101953 Pantai Cermin - Henny Sartika; Rizka Harfiani; Widy Masitah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This research aims to determine the role of the school community in fostering students' multicultural awareness through Islamic Religious Education (PAI) learning at SD Negeri No. 101953 Pantai Cermin, Serdang Bedagai Regency. The research approach used in this study is qualitative research with a case study method. Data were collected through observation, interviews, and documentation involving the school principal, teachers, students, and parents. The data were then analyzed using the steps of data collection, data condensation, data presentation, and conclusion drawing. The qualitative data analysis technique was applied with the aid of NVivo software. The results of this study show that the school community plays an active role in creating an inclusive and harmonious learning environment. This is reflected in the integration of multicultural values into both intracurricular and extracurricular activities, as well as the habituation of tolerance and appreciation for differences. This is achieved through their educative role, exemplary role, collaborative role, and facilitator role. The Islamic Religious Education teacher is the primary agent for internalizing